Economic Institutions and Comparative Economic Development: A Post-Colonial Perspective. (August 2017) - Bennett, Daniel L.; Faria, Hugo J.; Gwartney, James D.; Morales, Daniel R.
Highlights: Develop novel identification strategy to estimate the effect of institutions on economic development in former colonies. Identification accounts for both settlement conditions and colonizer identity, treating them as complements rather than substitutes. Use Economic Freedom of the World index as measure of broad cluster of mutually reinforcing economic institutions. Provide robust evidence that institutions exert a strong, positive, and potentially causal impact on log real GDP per capita. Geography (i.e., malaria ecology) exerts both direct and indirect effects via institutions on economic development. Summary: Existing literature suggests that either colonial settlement conditions or the identity of colonizer were influential in shaping the post-colonial institutional environment, which in turn has impacted long-run economic development. These two potential identification strategies have been treated as substitutes. We argue that the two factors should instead be treated as complementary and develop an alternative and unified IV approach that simultaneously accounts for both settlement conditions and colonizer identity to estimate the potential causal impact of a broad cluster of economic institutions on log real GDP per capita for a sample of former colonies. Using population density in 1500 as a proxy for settlement conditions, we find that the impact of settlement conditions on institutional development is much stronger among former British colonies than colonies of the other major European colonizers. Conditioning on several geographic factors and ethno-linguistic fractionalization, our baseline 2SLS estimates suggest that a standard deviation increase in economic institutions is associated with a three-fourth standard deviation increase in economic development. Our results are robust to a number of additional control variables, country subsample exclusions, and alternative measures of institutions, GDP, and colonizer classifications. We also find evidence that geography exerts both an indirect and direct effect on economic development.